2015
DOI: 10.1038/srep09269
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of retinal layers' optical intensities on 3D optical coherence tomography for central retinal artery occlusion

Abstract: Optical coherence tomography (OCT) provides not only morphological information but also information about layer-specific optical intensities, which may represent the underlying tissue properties. The purpose of this study is to quantitatively investigate the optical intensity of each retinal layers in central retinal artery occlusion (CRAO). Twenty-nine CRAO cases at acute phase and 33 normal controls were included. Macula-centered 3D OCT images were segmented with a fully-automated Iowa Reference Algorithm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…Recently, optical coherence tomography (OCT) confirmed that this opacification and swelling of the posterior pole, sparing the foveola (CRS), represent an ischemic infarction of the inner retinal tissues 28. When the inner retinal tissues suffer an irreversible infarct, their optical density increases and shadows over the lower optical intensity of the outer retina 28…”
Section: Discussionmentioning
confidence: 99%
“…Recently, optical coherence tomography (OCT) confirmed that this opacification and swelling of the posterior pole, sparing the foveola (CRS), represent an ischemic infarction of the inner retinal tissues 28. When the inner retinal tissues suffer an irreversible infarct, their optical density increases and shadows over the lower optical intensity of the outer retina 28…”
Section: Discussionmentioning
confidence: 99%
“…1). Likewise, all agree that the opacification and swelling of the posterior fundus, sparing the foveola, represents ischaemic infarction of the inner retinal tissues, as confirmed by the thickening and hyperreflectivity of the inner retinal layers seen on optical coherence tomography (OCT) (Chen et al, 2015). Significant differences of opinion have arisen, however, regarding the 3-dimensional extent of infarction induced by CRAO.…”
Section: Three-dimensional Extent Of Ischaemic Infarction After Craomentioning
confidence: 99%
“…The majority of researchers recommend the administration of steroids during treatment. There are reports concerning improvement of visual acuity after the use of steroid therapy; however, there are no randomised studies confirming the effectiveness of such a management [18,[26][27][28]. In our case, after steroids treatment visual acuity in the right eye improved from the level of counting fingers at 0.5 m to 0.3 m according to the Snellen scale.…”
Section: Discussionmentioning
confidence: 55%
“…In the presented case, the SD-OCT also revealed hyperreflective inner retinal layers, including the INL (Figure 3). It is presumed that increased reflectivity of the INL may be a marker of the extent of the ischaemia [18].…”
Section: Discussionmentioning
confidence: 99%